Meningkatkan Kemampuan Mengenal Warna Dengan Metode Eksperimen Warna Pada Kelas II SD Negeri Pleret Lor - Tri Asih; Insanul Qisti Barriyah (PT. ALHAFI BERKAH INDONESIA, 2023)
This study seeks to enhance the capacity for identifying primary and secondary colors through the utilization of experimental techniques that can foster students' cognitive faculties and bolster the efficacy of the learning process. The experimental method is an instructional approach in which students engage in doing experiments, observing the process, recording the experiment's outcomes, and subsequently presenting and having their observations evaluated by the teacher. The study methodology employed is descriptive qualitative research. The employed data collection techniques encompassed observation and interviews. The research findings indicate that students' proficiency in generating secondary colors is enhanced when experimental approaches are employed. Through the utilization of the experimental approach, students have the ability to generate secondary colors based on their individual preferences. In addition, the experimental method enhances pupils' confidence in color recognition. The students successfully created 15 secondary colors by combining primary colors with either primary colors or secondary colors.